EKSISTENSI HUKUM ADAT MASYARAKAT KAMPUNG NAGA (HUKUM NASIONAL, HUKUM WARIS ADAT, HUKUM TANAH ADAT, DAN HUKUM PERNIKAHAN ADAT) - Itok Dwi Kurniawan; Hassan Suryono (Program Pascasarjana Fakultas Hukum Universitas Sebelas Maret Surakarta, 2018)
AbstractThe article is aimed to understand the customary laws that which is retained in Kampung Naga relating to the national law or the law of nations. The kind of research in the article this is a doctrinal, while the whole including research evaluative. Based on the results of research and discussion can be explained that the indigenous people of Kampung Naga is an example of a that indigenous people still remain in existence in this era of globalization that are becoming increasingly are unstoppable again. The public confidence will adat law that has been read our being fortified for the community to prevent the entrance of foreign culture to Kampung Naga. The arrangement of spatial planning and the division of the adat land which are fair for the community make the community can live with peace and is carried out to keep the balance of nature. It is therefore need to appreciation to the indigenous people of Kampung Naga for their efforts from the government under the Kampung Naga made their customary village so public can regulate his life by independently of the people come from. The recommendation is 1) The government in this case the President or the Minister concerned should further specify the provisions on